Data Boxes as a Part of the Strategic Concept of Computerization of Public Administration in the Czech Republic - Jiří Dušek (Administrative Sciences, 2023)
The paper focuses on the analysis of the computerization of public administration in the Czech Republic in the context of the implementation and operation of data mailboxes, which have been an integral and very important part of e-Government in that country since 2009. A data mailbox has been defined in the Czech legal system since 2009 as an electronic repository of a special type established under the relevant Act No. 300/2008 Coll., which is intended for delivering electronic documents between public authorities on the one hand and natural persons and legal entities on the other. The data mailbox is mandatory for public authorities, legal entities registered in the Commercial Register, and natural persons engaged in business and may also be established by individuals not engaged in business. Public authorities are obliged to send documents preferably to the data mailbox of an addressee, if the latter has set up one, and, considering the legal assumption of delivery, entities which have set up a data mailbox are de facto obliged to collect documents from it. The aim of the study is a detailed description and critical analysis of the data mailbox system in the Czech Republic. The study also focuses on understanding the specific aspects of the implementation of data mailboxes in the Czech Republic. The main methods used are description, thematic and comparative analysis, so this is a descriptive case study. The results of the analysis confirm a number of problems related to the operation of data mailboxes, whether they be technical problems, security risks, usability problems, legal and regulatory problems or other organizational and procedural problems. The forced “computerization” of communication of a number of legal entities in 2023 is also mentioned.